تطبيق التعليم المخارج الحروف في ترقية مهارة الكلام - Abu Bakar, M. Yunus; Huda, Hisbullah; Farikhah, Fatiya Nur; Hanifah, Umi (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Language is one of the needs of society in communicating with a variety of applications to be carried out. However, many students have difficulty in applying speaking skills using Arabic. This study aims to determine the application of education in improving Arabic speaking skills. Analysis The research method used is a quantitative method through the process of collecting digital data. This research uses descriptive research with field study method. Speaking skill is one of the language skills that must be achieved in modern language teaching. Many learners rely on learning correct pronunciation on imitation from the teacher, and while acknowledging the safety and accuracy of the teacher’s pronunciation, they need organized training in imitating sounds and their output, and therefore the teacher should not leave the opportunity in which he or she helps his students to produce new and strange sounds. The application of cursive learning in developing students’ speaking skills includes direct methods such as explaining Arabic sounds and how to get them out by instructing students to distinguish Arabic sounds that have a representative exit. the effectiveness of the application of Cursive Learning in improving speaking skills in teaching Arabic through the evaluation process of teachers, one of which is in pronouncing students’ voices and identifying difficult language sounds to pronounce.